Sistem kewangan Islam di Malaysia: perlukah ke mahkamah syariah? - Jasri Jamal ,; Ruzian Markom , (Fakulti Undang - Undang, 2010)
On 31st March 2009, Court of Appeal has revoked the decision made by High Court to announce that the contract of Bay Bithaman Ajil is null and void in the case of Arab- Malaysia v Taman Ihsan Jaya Sdn. Bhd. & Onor [2008] 5 MLJ 631. Interestingly, the judgement made by Appeal Court has touched the basic elements of Islamic law especially the fundamental issues of BBA such as sell and buy contract, acceptance of difference views of school of laws in Islam and other basic issues of Shari’ah principles. This subject matter of Shari’ah principles should be decided the Syariah judges who are more expert in Islamic law than the civil court. This paper is looking into legal ramework of Islamic Financial System in Syariah court jurisdiction as well as Civil Court